1986
DOI: 10.1038/ki.1986.194
|View full text |Cite
|
Sign up to set email alerts
|

A new method for studying human polycystic kidney disease epithelia in culture

Abstract: Human polycystic kidney disease (PKD) epithelia were successfully grown in culture and expressed abnormal characteristics. Cysts lining epithelia of superficial and deep cysts were microdissected and compared to individual normal human proximal straight tubules (PST) and cortical collecting tubules (CCT) grown in defined media. PKD cyst epithelia differed from normal renal tubular epithelia in growth patterns and structural and functional properties. PKD epithelia grew more rapidly and showed cyst-like areas i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(47 citation statements)
references
References 22 publications
3
44
0
Order By: Relevance
“…The mechanism behind this decreased urine concentrating capacity is not known, but it is suggested to have a renal origin. The impaired ability to reabsorb water could be secondary to cystinduced abnormality in renal architecture, leading to an impaired medullary osmotic gradient (15) or to insensitivity to AVP (e.g., due to a receptor defect) (4,16). Theoretically, a lower renal concentrating capacity could also have a central cause (i.e., impaired AVP release by the pituitary gland).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism behind this decreased urine concentrating capacity is not known, but it is suggested to have a renal origin. The impaired ability to reabsorb water could be secondary to cystinduced abnormality in renal architecture, leading to an impaired medullary osmotic gradient (15) or to insensitivity to AVP (e.g., due to a receptor defect) (4,16). Theoretically, a lower renal concentrating capacity could also have a central cause (i.e., impaired AVP release by the pituitary gland).…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Primary cells taken from nephrectomized ADPKD kidneys have been linked to various epithelial cell phenotypes, but because these cells are derived from kidneys with advanced disease, it remains unclear whether these characteristics represent primary defects central to PKD etiology or secondary consequences of injury or dedifferentiation. 6,[18][19][20][21] A powerful new technology, induced pluripotent stem (iPS) cells are adult somatic cells which have been reprogrammed into an embryonic pluripotent state. 22,23 The result is a next generation cell culture model that can differentiate into diverse cell types and complex tissues for the purposes of regenerative therapies or investigating disease.…”
mentioning
confidence: 99%
“…Also, they observed that nearly every cyst had an abnormal basement membrane. In 1986, Patricia Wilson and her colleagues observed that human PKD epithelial cells in culture exhibited an extremely abnormal basement membrane morphology consisting of some banded collagen and numerous unique blebs or spheroids (Wilson et al, 1986). These blebs stained with ruthenium red, suggesting a proteoglycan component.…”
Section: Early Observations Of Ecm Abnormalities In Pkdmentioning
confidence: 99%